A rare case of coexistence of metastasis from head and neck squamous cell carcinoma and tuberculosis within a neck lymph node. Issue 1 (December 2015) - Caroppo, Danila; Russo, Daniela; Merolla, Francesco; Ilardi, Gennaro; Del Basso de Caro, Marialaura; Di Lorenzo, PierPaolo; Varricchio, Silvia; Mascolo, Massimo; Staibano, Stefania
Abstract Coexistence of metastasis from squamous cell carcinoma and tuberculosis within lymph nodes is rare. We report a case of 86 years old woman with a mass in the left laterocervical region. The patient had undergone excision of a poorly differentiated squamous cell carcinoma from the mucosa of the left cheek, a few months before. Histological examination of a mass of few fused lymph nodes, isolated from left laterocervical lymphadenectomy, showed metastatic squamous cell carcinoma with concomitant granulomatous inflammation. A diagnosis of tuberculosis associated with malignancy was posed. The suspect was confirmed by a positive anamnestic finding of a previous tuberculosis infection. The granulomatous reaction may be associated with many types of tumor, and can be found in the draining lymph nodes. The possibility that this reaction is also due to a tuberculosis infection should be kept in mind for elderly oncology patient.